2005
DOI: 10.1255/jnirs.561
|View full text |Cite
|
Sign up to set email alerts
|

Nutritive Evaluation of Forages by near Infrared Reflectance Spectroscopy

Abstract: El artículo seleccionado no se encuentra disponible por ahora a texto completo por no haber sido facilitado todavía por el investigador a cargo del archivo del mismo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 79 publications
(81 reference statements)
0
17
0
2
Order By: Relevance
“…Laboratory analysis of pasture samples has been facilitated by developments in near infrared spectroscopy (NIRS) to analyse a wide array of chemical, physical and morphological attributes of forages (Andres et al, 2005;Landau et al, 2006). This includes capacity to measure morphological attributes such as the leaf-to-stem proportions, which are particularly important in tropical grass pastures, the proportions of major plant groupings (Garcia-Criado et al, 1991;Pilon et al, 2010), and to some extent of specific plant species (Coleman et al, 1990;Atkinson et al, 1996).…”
Section: Evaluation Of Pasture Attributesmentioning
confidence: 99%
“…Laboratory analysis of pasture samples has been facilitated by developments in near infrared spectroscopy (NIRS) to analyse a wide array of chemical, physical and morphological attributes of forages (Andres et al, 2005;Landau et al, 2006). This includes capacity to measure morphological attributes such as the leaf-to-stem proportions, which are particularly important in tropical grass pastures, the proportions of major plant groupings (Garcia-Criado et al, 1991;Pilon et al, 2010), and to some extent of specific plant species (Coleman et al, 1990;Atkinson et al, 1996).…”
Section: Evaluation Of Pasture Attributesmentioning
confidence: 99%
“…On the other hand, feed industry relies strongly on IR reflectance spectroscopy as an alternative to wet chemistry Workman and Shenk, 2004). IR reflectance spectroscopy is a fast, reliable and cost-effective way to predict feedstuffs' chemical composition (Andrés et al, 2005a) and it is used in combination with mathematical models to formulate diets for cattle . Recently, Belanche et al (2013 and2014) used Fourier transformation mid-IR spectroscopy (FTIR) to estimate degradability parameters of CP, dry matter (DM) and NDF, and results suggested that mid-IR can be used for screening purposes but not for estimating dynamic parameters of degradability.…”
Section: Introductionmentioning
confidence: 99%
“…However, chemical analyses are expensive and inappropriate for breeding purposes. In contrast, physical analysis by laboratory near‐infrared spectroscopy is less expensive and has become a successful alternative for determination of chemical composition and nutritional attributes of silage corn hybrids (Andrés et al. 2005).…”
mentioning
confidence: 99%